Therapeutic efficacy of anti‐dandruff shampoos: A randomized clinical trial comparing products based on potentiated zinc pyrithione and zinc pyrithione/climbazole. (24th May 2013) - Schwartz, J. R.; Bacon, R. A.; Shah, R.; Mizoguchi, H.; Tosti, A.
Synopsis Objectives Dandruff is a chronic, relapsing scalp condition that negatively impacts the quality of life of sufferers. Regular use of anti‐fungal shampoos represents a proven therapeutic strategy to improve the most common symptoms of flakes and itch. Two recent approaches for enhancing the efficacy of anti‐fungal shampoos are maximizing bio‐availability of the active material or the addition of a second active material. Our aim is to compare the therapeutic efficacy of these two approaches – maximization of bio‐availability of the zinc pyrithione (ZPT) active material or the combination of ZPT with a secondary active material. Methods The anti‐fungal potency of shampoos representing each of these approaches was evaluated in vitro using a standard microbiology method. Spatial delivery of ZPT particles in the follicular infundibulum was assessed in vivo using a novel confocal microscopy methodology. Clinical efficacy was assessed in a randomized, double‐blind trial involving 620 male and female subjects using scalp flaking and epidermal histamine level as endpoints. Results The shampoo formula with maximized ZPT bio‐availability known as the Potentiated ZPT formula exhibited greater anti‐fungal potency than the Dual Active shampoo containing both ZPT and climbazole. The Potentiated ZPT formula also delivered more ZPT to the lower infundibulum than the Dual Active shampoo. A 4‐week treatment with the Potentiated ZPT formula resulted in superior clinical efficacy compared with the Dual Active product at all 4 weekly time points for both flaking and epidermal histamine endpoints. Conclusion These results highlight the critical role that the shampoo vehicle plays in realizing full potency of active materials. By optimizing the delivery vehicle, the enhanced anti‐fungal potency and the maximized spatial delivery of active materials result in greater symptomatic improvement than a product with two active materials. The therapeutic efficacy of a product based on a complex delivery vehicle such as a shampoo must be considered from a full‐product perspective rather than just the active system as the non‐active components of the composition will often play a significant role in the overall product pharmacology and resultant efficacy.